2017
DOI: 10.1136/bmjopen-2017-017144
|View full text |Cite
|
Sign up to set email alerts
|

Impact of child summertime obesity interventions on body mass index, and weight-related behaviours: a systematic review and meta-analysis protocol

Abstract: IntroductionIn previous studies, it has been found that on average, children consistently gained weight during the summer months at an increased rate compared with the 9-month school year. This contributed to an increased prevalence of overweight and obesity in children. Several obesity-related interventions have occurred during or targeting the summer months. We propose to conduct a systematic review and meta-analysis of the impact of obesity prevention and treatment interventions for school-age children cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Studies have shown that compared to other months during the school year, weight gain during the summer months is significantly higher, and contributed to increased prevalence of overweight and obesity in children. 13,14 This study revealed that the proportion of children who were either overweight or obese increased from 23.9% to 31.4%. Also, children that were in the normoweight category experienced significant increase in BMI z-scores, and almost 10% of normoweight children moved up into the overweight or obese category.…”
Section: Discussionmentioning
confidence: 88%
“…Studies have shown that compared to other months during the school year, weight gain during the summer months is significantly higher, and contributed to increased prevalence of overweight and obesity in children. 13,14 This study revealed that the proportion of children who were either overweight or obese increased from 23.9% to 31.4%. Also, children that were in the normoweight category experienced significant increase in BMI z-scores, and almost 10% of normoweight children moved up into the overweight or obese category.…”
Section: Discussionmentioning
confidence: 88%
“…Interventions designed for the free time of the child such as after school programs or summer camps showed to be successful in preventing overweight and obesity, increasing the consumption of fruit and vegetables intake, increasing physical activity, and showing statistical differences in some of the weight related outcomes (Moreno, Vézina-Im, Vaughan, & Baranowski, 2017). Findings suggests that summer camp based childhood obesity prevention programs may be successful in fighting childhood obesity.…”
Section: Discussionmentioning
confidence: 90%